ANALISIS BAHASA TABU PADA DIALEK MELAYU LABUHAN BATU UTARA - Gumarpi Rahis Pasaribu; Mubshirah, Dara (Yayasan Insan Cipta Medan, 2025)
This study discusses taboo language in the Panai Malay dialect spoken in North Labuhan Batu Regency, North Sumatra. The study aims to describe the forms of taboo language used by the Panai Malay community and explain the social and cultural factors influencing its use in daily communication. This research employed a descriptive qualitative method with a sociolinguistic approach. The data consisted of taboo words and expressions collected through observation, interviews, and documentation techniques involving members of the Panai Malay community. The data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings reveal that taboo language in the Panai Malay dialect is still frequently used in informal communication, especially among peers and in emotional situations. The taboo expressions found in this study include categories related to insults, body parts, biological activities, supernatural beings, and social morality. Several taboo words identified include mampus, bengak, gilo, pukimak, berak, kencing, lonte, and jalang. The use of taboo language is influenced by age, social relationships, communication context, and community cultural values. In Panai Malay society, taboo language is considered impolite because it contradicts the values of politeness and courtesy upheld in Malay culture. This study concludes that taboo language in the Panai Malay dialect reflects the close relationship between language, culture, and social norms within the community. In addition to functioning as emotional expression, taboo language also serves as a form of social control and cultural identity in the Panai Malay community.